Gamification of Learning in Early Age Education - Houang Mui Lee; Phung Anh Loo (Journal La Edusci, 2021)
Gamification teaches children many new abilities at a young age. It also increases their emotional well-being and emotional intelligence. Gamification enables your kid to study in a distraction-free atmosphere in a familiar setting. Gamification helps foster a positive attitude toward learning by creating engaging, personalized, and amusing learning materials. The majority of educational learning applications include unique music that will aid language development. Gamification allows your kid to study and participate at their own speed, free of peer or teacher pressure